2009
DOI: 10.3390/ma2041895
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ceramics as Bone Substitutes in Revision Hip Arthroplasty

Abstract: The number of grafting procedures, including those performed in primary and revision hip arthroplasty, continues to rise around the world. Demand for musculoskeletal donor tissue now outstrips supply. There is no single bone substitute that is ideal for all circumstances. Bone substitutes act as a scaffold and are usually osteoconductive. They are rarely osteoinductive; if they are, a molecular bond is formed between the graft and host bone, improving fixation and longevity. Bone graft substitutes are very rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Nevertheless, to overcome the limitations of these treatments, especially those related to the lack of availability of patient/donor tissue, synthetic or semi-synthetic materials have been demonstrated to be valid alternatives for the replacement of natural bone stock [ 16 , 17 , 18 , 19 , 20 , 21 ]. Among these, absorbable ceramics such as hydroxyapatite (HA), calcium sulphate, and tricalcium sulphate (TCP), or their combination, are commonly used as bone grafts [ 22 ]. Notably, HA is a major component of natural bone and can favour new bone formation while acting as a scaffold in the implanted site.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to overcome the limitations of these treatments, especially those related to the lack of availability of patient/donor tissue, synthetic or semi-synthetic materials have been demonstrated to be valid alternatives for the replacement of natural bone stock [ 16 , 17 , 18 , 19 , 20 , 21 ]. Among these, absorbable ceramics such as hydroxyapatite (HA), calcium sulphate, and tricalcium sulphate (TCP), or their combination, are commonly used as bone grafts [ 22 ]. Notably, HA is a major component of natural bone and can favour new bone formation while acting as a scaffold in the implanted site.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 It seems that the inorganic phosphate was not removed during purification. As a result, there was an increase in the similarity to the mineral components of natural bones, 34 which will be advantageous for its use as a bone graft material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that calcium ions are concentrated in coccolithophore cells and that coccolith production is regulated by phosphate availability. , It seems that the inorganic phosphate was not removed during purification. As a result, there was an increase in the similarity to the mineral components of natural bones, which will be advantageous for its use as a bone graft material.…”
Section: Resultsmentioning
confidence: 99%
“…No risk of transmitting disease plus immunogenicity after implantation are the major advantages of the ceramics [31]. Other remarkable advantages are higher resistance to compressive force, low toxicity, good corrosion resistance, and promotion of the formation of new hard tissues.…”
Section: Ceramicsmentioning
confidence: 99%